Memasyarakatkan Al-Qur’an Perspektif Quraish Sihab : (Studi Analisis Surah Al-Fatir: 29) - Moh. Fajar (Reflection : Islamic Education Journal, 2025)
This study aims to examine Quraish Shihab's understanding and perspective in popularizing the Qur'an, focusing on Surah Al-Fatir: 29. This surah was chosen because it contains an important message about the role of reading and understanding the Qur'an in everyday life. In this study, a qualitative approach with analysis of the interpretation text is used to explore the meaning and relevance of the verse according to Quraish Shihab. This study found that Quraish Shihab emphasized the importance of reading the Qur'an with full appreciation, not only as a ritual activity, but also as a life guide that can be applied in social life. He also invited Muslims to make the Qur'an a source of inspiration in facing the challenges of the times. Through this understanding, society is expected to be closer to the Qur'an and apply its teachings in everyday life. This study contributes to the understanding of contemporary interpretation, as well as promoting the importance of popularizing the Qur'an as a relevant and applicable life guide.